EFFECT OF 'BRUSH YOUR TEETH' SONG ON DENTAL AND ORAL HEALTH OF DOWN SYNDROME CHILDREN - Emanuela Marchellina; Galuh Dwinta Sari; Renie Kumala Dewi; Aulia Azizah; Rahmad Arifin (FKG ULM, 2025)
Background: Down syndrome children are a group of children with special needs caused by abnormalities in chromosomes that result in loss of skills and brain function. Songs are innovative health promotion media, songs can help children with Down syndrome increase motivation, concentration, perceptual abilities, as well as retention and memory skills including oral health behavior. Objective: Knowing the effect of using the song